Guía de estudio como recurso didáctico para el aprendizaje de Biología Vegetal con estudiantes de tercer semestre de la carrera de Pedagogía de las ciencias Experimentales Química y Biología - Llamba Quinllin, Monica Alexandra (2024)
A study guide is a didactic resource that contributes to the learning of Plant Biology as it is an educational resource that helps to improve the understanding and retention of the concepts of the subject, integrating various resources such as mind maps, infographics and experimental activities, the research had as a problem the lack of student interest in the subject, in addition to the use of study guide is scarce. For this reason, the objective of this research work was to propose a study guide as a didactic resource for the learning of Plant Biology with third semester students of the Pedagogy of Experimental Sciences, Chemistry and Biology. This study applied a quantitative approach methodology with a nonexperimental design, descriptive, exploratory scope, basic for the objective, field and bibliographic for the place, the type of study was transversal. We worked with a population of 32 third semester students. After analyzing the results, it was possible to verify the degree of favorable satisfaction with the study guide, which contributes and favors better learning by relating theory and practice, and the proposal was well received and of great interest among the students.